Associação entre capacidade funcional e fatores sociodemográficos, econômicos e de condições de saúde em idosos comunitários de Belo Horizonte (MG), Barueri (SP), Santa Cruz (RN): estudo da rede fibra - Ana Cisalpino Pinheiro (2015)
Population aging is a global phenomenon of great intensity in the Brazilian population. Among the main commitments arising from aging with multimorbidities is functional disability. It is a multifactorial condition of adverse outcomes that can be influenced by environmental and personal factors. The aim of this study was to investigate the association between the instrumental activities of daily living (IADL) and socio-demographic, economic factors and health conditions in community-dwelling elderly in the cities of Belo Horizonte, Barueri and Santa Cruz, within data FIBER Network (Network Studies of Fragility in Elderly Brazilians) obtained from UFMG pole. The sample consisted of 1334 elderly aged 65 years or more without cognitive deficits and able to walk independently. Functional capacity was assessed by items from the Lawton scale for AIVD. The independent variables were evaluated from standardized multidimensional inquiry by FIBER network, grouped into two investigative blocks: sociodemographic and economic variables; the variables related to health conditions. Descriptive analysis was performed using measures of central tendency and dispersion for continuous variables, absolute frequency (n) and relative (%) for categorical variables to characterize the sample. Then analysis was applied, using the chi-square test of Pearson. The variables with p <0.05 were included in the models of binary logistic regression. The majority of the sample was considered independent in IADL with an average of 81% of independence for each IADL investigated. The sample was composed mostly of women (64.17%, n = 856), with a mean age of 73.36 ± 6.35 years, mostly in the age group 65-74 years old, living alone , low education and chronic diseases. Regarding the distribution of impairment frequency in performing each AIVD identified that around 20% of the elderly had some difficulty using the phone, use transport, handling drugs and money, shopping, performing household chores and prepare food. Logistic regression identified that women are more likely to present reliance on AIVD than men, and older seniors (85 and over), those who had more multimorbidities and those who rated their health as bad or very bad. By analyzing each IADL instrument separately, rather than a summed score, this study brought an analytical advantage to the theme, contributing to understand the associations between selected dependent variables and the measured outcomes intrinsically, which amplifies the evidence been found . Another aspect that contributes to the advancement of knowledge, is the stratification of the sample in groups of younger and older seniors, allowing demonstrate that advancing age is an important factor associated with functional disability and that should be considered in approaches health outcomes of older people. This data can contribute to the establishment of therapeutic actions and public policies to improve the management and disability prevention in the elderly.